Propofol Mediated Protection of the Brain From Ischemia/Reperfusion Injury Through the Regulation of Microglial Connexin 43 - Zhang, Tingting; Wang, Yanyan; Xia, Qin; Tu, Zhiyi; Sun, Jiajun; Jing, Qi; Chen, Pei; Zhao, Xuan (Frontiers in Cell and Developmental Biology, 2021)
Cerebral ischemia/reperfusion (I/R) injury is a serious condition that leads to increased apoptosis of microglial and neurons in the brain. In this study, we identified that Cx43 expression level is significantly increased in the microglial cells during I/R injury. Using an in vitro model (hypoxia/reoxygenation-H/R injury), we observed that H/R injury leads to an increase in activation of microglial cells and increase in levels of pro-inflammatory markers such as IL-1β, IL-6, and TNF-α. Additionally, we could also observe significant increase in phosphorylation of Cx43 and Cav3.2 levels. To assess the role of H/R injured microglial cells on neuronal population, we cultured the neurons with conditioned media (MCS) from H/R injured microglial cells. Interestingly, we observed that microglial H/R injury significantly decreased Map2 expression and affected neuronal morphology. Further, we aimed to assess the effects of propofol on cerebral H/R injury, and observed that 40 μM propofol significantly decreased Cx43, Cx43 phosphorylation, and CaV3.2 levels. Additionally, propofol decreased apoptosis and increased Map2 expression levels in in H/R injured neurons. Using silencing experiments, we confirmed that siCx43 could significantly improve the propofol’s rescue after H/R injury in both microglia and neurons. We further developed an in vivo MCAO (middle cerebral artery occlusion) rat model to understand the effect of propofol in I/R injury. Interestingly, propofol treatment and downregulation of Cx43 significantly decreased the infract volume and apoptosis in these MCAO rats. Thus, this study clearly establishes that propofol protects the brain against I/R injury through the downregulation of Cx43 in microglial cells.